Combination of macroalgae-conditioned water and periphytic diatom Navicula ramosissima as an inducer of larval metamorphosis in the sea urchins Anthocidaris crassispina and Pseudocentrotus depressus - Jing-Yu, Li; Siti Akmar Khadijah, Ab Rahim; Satuito, Cyril Glenn; Kitamura, Hitoshi (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The induction of larval metamorphosis in the sea urchins Anthocidaris crassispina and Pseudocentro(us depressus was investigated in the laboratory, using waters conditioned by 15 different macroalgae combined with the periphytic diatom Navicula ramosissima. Larvae of P. depressus did not metamorphose, but larvae of A. crassispina showed a high incidence of metamorphosis, especially in waters conditioned by coralline red algae or brown algae. High inductive activity for larval metamorphosis was detected in Corallina pi/ullfera-conditioned water during a 2.5-year investigation, but the activity was relatively low in February or March and in September, the off-growth seasons of the alga. By contrast, Ulva pertusa-conditioned water did not show metamorphosis-inducing activity except in spring or early summer. These results indicate that during their growth phase, red and brown algae release into their environment active substances that are involved in the larval metamorphosis of A. crassispina.